The producer's lot: what to consider in production - Burrett, Alex (Henry Stewart Talks, 2008)
What to consider in radio production, Timing the script, Legal Issues, Technical and casting, Overseeing production and directing talent, Dealing with feedback
Archived at 2022/03/17